The genus Helianthus L. in the Russian Far East and in East Asia - E. V. Lesik; I. A. Kreshchenok; G. V. Talovina (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. By now, Helianthus L. spp. have spread out to many parts of the world as cultivated or adventive plants. Herbarium collections, published sources, and our own data were used to study the emergence, distribution, environmental patterns, and adaptation of 6 species and 1 subspecies of Helianthus L. in the Russian Far East and in East Asia.Materials and methods. Field studies in the Russian Far East were carried out using the route-based method from 2001 through 2022 over Amur Province, and Khabarovsk and Primorsky Territories. The data for the entire area of studies were retrieved from published sources and official web databases. Maps with Helianthus growing sites were made using the MapInfo software. Results and conclusions. Changes in environmental conditions contributed to the expansion of the range of H. annuus L. and H. tuberosus L. Actively cultivated in the Russian Far East and in East Asia, these two species are obviously quite localized to areas with a mild, warm and humid climate. Other Helianthus spp. are distributed to a much lesser extent, being in most cases poorly adapted to uncultivated growth in the Russian Far East or East Asia. Increased occurrence of H. annuus subsp. lenticularis (Douglas ex Lindl.) Cockerell in agrocenoses of Amur Province is probably associated with underpurified soybean material. Higher distribution of H. strumosus L. across ruderal communities in Japan, contrary to the other studied areas, is likely to have been induced by specific climate conditions. On the whole, the physical geography, the pace and degree of anthropogenic pressure, and the climate change impacts in East Asia and the Russian Far East favored successful naturalization, albeit uneven distribution, of H. annuus and H. tuberosus in various disturbed communities, in contrast to H. rigidus (Cass.) Desf., H. laetiflorus Pers., or H. petiolaris Nutt.